The Contribution of Astronomy in Determining the Direction of the Qibla and the Hijri Calendar in the 8th–14th Centuries CE - Abdullah, Choirul; Falah , Muhammad; Taufiqurrahman, Taufiqurrahman; Abdullah, Mahfazul Alam bin (Yayasan Albahriah Jamiah Indonesia, 2025)
Astronomy from the 8th to 14th centuries CE played a crucial role in meeting the practical needs of Muslims, particularly in determining the direction of the Qibla and establishing the Hijri calendar, which requires precise geographical orientation and timing of worship. Although the traditional practice of rukyat (seeing the sun) has been used, modern literature has not systematically evaluated the contribution of classical astronomy theories and instruments to the accuracy of worship and religious administration. This study aims to describe the contributions of classical astronomers, such as al-Khwārizmī, al-Battānī, al-Bīrūnī, Naṣr al-Dīn al-Ṭūsī, Ibn Yūnus, and Ibn Shāṭir, in the development of instruments, observation methods, and mathematical calculations, and to evaluate their influence on the accuracy of the Qibla direction and the Hijri calendar. The technique used is qualitative-historical, with the exploration of classical astronomical works, manuscripts, and contemporary literature, analyzed critically and hermeneutically to assess astronomical instruments’ methodological innovation and accuracy. The results of the study show that astronomical scientists such as al-Khwārizmī, al-Battānī, al-Bīrūnī, Naṣr al-Dīn al-Ṭūsī, Ibn Yūnus, and Ibn Shāṭir succeeded in developing the theory of spherical trigonometry, methods for measuring the sun’s shadow, and observation instruments such as astrolabes and mural quadrants, thus ensuring the accuracy of the direction of the Qibla in various Islamic regions. In the context of the Hijri calendar, their innovations resulted in more accurate astronomical calculations to determine the beginning of the month, reducing dependence solely on traditional rukyat and supporting state administration and navigation. In conclusion, the contribution of classical astronomy was not only practical in supporting ritual needs but also provided a methodological foundation for modern astronomy, emphasizing the importance of integration between empirical observation and mathematical theory in the development of Islamic science.